Meta-Analysis: The Relationship between Financial Literacy and Investment Decisions: English - Yunus, Michael Gregory; Tanesia, Cindy Yoel (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2026)
Financial literacy is the important element in healthy personal financial management, especially with the increasing accessibility of various investment products and instruments in Indonesia. Financial technology development, banking system digitalization, and retail investor growth are pushing the improvement for adequate financial literacy. However, the level of financial literacy in Indonesia is relatively considered low, especially among young generations and people living outside the urban areas. Financial literacy affects individuals’ investment decisions, and thus, the low level of financial literacy may affect the quality of their investment decision. This study conducted a meta-analysis of 57 empirical studies to examine the relationship between financial literacy and investment decisions. Using comprehensive meta-analysis v3 software, this study calculated the summary of correlation, examined the heterogeneity between studies, and evaluated the possibility of publication bias. Meta-analysis results showed the positive relationship between financial literacy and investment decision with correlation of 0.357. The high heterogeneity indicated that the effectiveness of financial literacy is influenced by respondent characteristics and measurement methods used in each study. The findings provide a strong scientific basis for a more effective and segmented financial literacy program development according to the various needs of Indonesian citizens. Financial literacy education programs need to consider social context and investment experience for optimal results.